Individual attitudes towards immigrants: welfare-state determinants across countries - Giovanni Facchini; Anna Maria Mayda (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper analyzes welfare-state determinants of individual attitudes towards immigrants - within and across countries - and their interaction with labor-market drivers of preferences. We consider two different mechanisms through which a redistributive welfare system might adjust as a result of immigration. Under the first scenario, immigration has a larger impact on individuals at the top of the income distribution, while under the second one it is low-income individuals who are most affected through this channel. Individual attitudes are consistent with the first welfare-state scenario and with labor-market determinants of immigration attitudes. In countries where natives are on average more skilled than immigrants, individual income is negatively correlated with pro-immigration preferences, while individual skill is positively correlated with them. These relationships have the opposite signs in economies characterized by skilled migration (relative to the native population). Such results are confirmed when we exploit international differences in the characteristics of destination countries' welfare state.
Keywords: F22; F1; J61; 330; Einwanderung; Sozialstaat; Theorie; USA